2004
DOI: 10.1158/1078-0432.ccr-04-0722
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Expression Profiles of Squamous Cell Carcinoma of the Head and Neck Correlate with Cisplatin Sensitivity and Resistance in Cell Lines and Patients

Abstract: Purpose: The choice of treatment for squamous cell carcinoma of the head and neck (SCCHN) is still primarily based on the tumor-node-metastasis classification. However, it is reasonable to believe that biological profiles of SCCHN may be independently associated with response to therapy. The aim of the present study was to examine genetic changes and gene expression profiles that might correlate with sensitivity to cisplatin [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay] in 10 SCCHN cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 33 publications
3
66
0
Order By: Relevance
“…Interestingly, when we further analyzed the preferred binding motifs for different NF-nB subunits, a predominance of p65 binding motifs were observed in the promoters of cluster B genes, in contrast to the prevalence of p50 and c-REL binding motifs present in the promoters of cluster A genes with putative NFnB binding sites. 5 Significant differences in the prevalence of TP53 and NF-nB p65 binding sites were detected between clusters A and B (Fig. 3C, m 2 , P < 0.05).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, when we further analyzed the preferred binding motifs for different NF-nB subunits, a predominance of p65 binding motifs were observed in the promoters of cluster B genes, in contrast to the prevalence of p50 and c-REL binding motifs present in the promoters of cluster A genes with putative NFnB binding sites. 5 Significant differences in the prevalence of TP53 and NF-nB p65 binding sites were detected between clusters A and B (Fig. 3C, m 2 , P < 0.05).…”
Section: Resultsmentioning
confidence: 86%
“…In head and neck squamous cell carcinomas (HNSCC), gene expression profiling has been used in an attempt to identify biomarker signatures for diagnosis (4), differential sensitivity to chemotherapy (5), risk of recurrence (6), survival (7), malignant phenotype (8), and metastasis (9). Although considerable variability in the composition of gene signatures was observed in these studies, the data provided evidence for subsets and heterogeneity within HNSCC, which are possibly related to differences in molecular pathogenesis and malignant potential.…”
mentioning
confidence: 99%
“…In addition, these techniques have also allowed for the identification of gene expression signatures that may help predict cisplatin sensitivity in various cancers (Akervall et al, 2004;Takata et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, significant numbers of resistant SCC cells emerge rapidly following initial cisplatin treatment. Thus, many retrospective clinical studies reported that cisplatin was unable to increase survival when administered as a monotherapy or in combination with surgery or radiotherapy (11)(12)(13). Cisplatin is a platinum-containing compound that induces DNA damage by binding to DNA and forming adducts that impair de novo synthesis.…”
mentioning
confidence: 99%